Effect of Used Motor Oil Contamination on Geotechnical Properties of Clay Soil on Uyo-Akwa Ibom - G.T, Akpabio; I.E, Udoinyang; T.S, Basil (International Journal of Natural Sciences Research, 2017)
This paper was carried to investigate the effect of used motor oil contamination on geotechnical properties of Clay soil in UYO-AKWA IBOM. In view of this, evaluating possible changes caused by waste motor oil spills in the environment and determining the suitability of some engineering construction materials in the area of study were made possible. The contaminated soil was prepared by adding different percentages of waste motor oil; 4%, 8%, 12% and 16%. The particle size distribution test (sieve analysis), compaction test, Atterberg limit test and California Bearing Ration (CBR) test were determined in both contaminated and uncontaminated sandy and clay soils. The result showed an increase in particle size distribution of soil after carrying out the analysis: reduction in optimum moisture content and maximum dry density for compaction test, reduction in liquid limit, and also a reduction in CBR value due to waste motor oil contamination. These show that the presence of waste motor oil has a remarkable effect on geotechnical properties of clay soils.